PERANCANGAN DAN SIMULASI PLTS ATAP 1 KWP MENGGUNAKAN HELIOSCOPE - I Gede Civavisna Brahma; I Nyoman Satya Kumara; Ida Ayu Dwi Giriantari (Program Studi Teknik Elektro UNUD, 2021)
Solar Power Plant (PLTS) as one of the renewable energy sources that is being focused on itsdevelopment. This article discusses the design and simulation of the performance of a 1 kWp rooftopsolar power plant using a Helisocope. The input data required by the Helioscope is PLTS technicalspecifications such as solar panel technology, inverter type, number and type of modules selectedand land area. The location data required by the PLTS system includes the coordinates, the type ofroof of the building, the environment around the PLTS and meteorological data. The 1 kWp PLTS roofsystem designed at the location that the author uses uses 7 pcs Canadian Solar 195 Wp panels, 1pcs 1 kW AEC inverter, installed on the roof of the building facing north, and connected to the PLNnetwork via a net meter. This 1 kWp rooftop PLTS is capable of producing an average daily averageof 5,48 kWh, 41,07 kWh weekly, 164,29 kWh monthly, and annual 1971,5 kWh. Energy productionvaries by an average of 8% per month with the minimum production in January of 135,1 kWh and thehighest in July of 184,5 kWh. The designed 1 kWp PLTS roof produces a performance ratio of 73,6%with the irradiation received in a year reaching 1859,2 kWh/m2. The initial investment required to builda 1 kwp PLTS roof is IDR. 20.000.000.